Investigasi Akuifer Air Tanah di Sekitar Lahan Pertanian Desa Kedungwuluh, Kecamatan Kalimanah, Kabupaten Purbalingga, Jawa Tengah Berdasarkan Survei Geolistrik Resistivitas dengan Konfigurasi Wenner - Sehah Sehah; Hartono Hartono (Jurnal Fisika FLUX, 2010)
Exploration to groundwater sources has been done at Kedungwuluh,District of Kalimanah, Regent of Purbalingga Central Java using GeoelectricResistivity method with Wenner configurations. This research done at around ofagriculture land in Kedungwuluh. The objective of this research is interpret todepth and properties of groundwater aquifer based on resistivity data of Wennerconfigurations. The lenght of measurement trajectory in this research area are300 meters, that outstretched from coordinate of 07° 23′ 46.5″ S and 109° 18′42,9″ E up to 07° 23′ 56″ S and 109° 18′ 42,9″ E. The results that obtained fromthis research is two dimensionly (2D) resistivity profile of sub surface rocks,which contains of some layers or section of rocks, i.e: sandy claystone (< 53,35m), clayey sandstone (53,35 up to 75,35 m), smooth sandstone (75,35 up to249,00 m), and compacted sandstone and gravel (>249,00 m). Based on theresults of the interpretation, estimated that rock section which most dominant asgroundwater aquifer is smooth sandstone, and then clayey sandstone, thensandy claystone. While compacted sandstone and gravel is not estimated asaquifer.